Exploring Writing Anxiety and Its Impact on TOEFL Performance Among Chinese Senior High School Students: Causes, Correlates, and Pedagogical Implications: A Mixed Methods Study - Jiang, Xue; Lu , Zhongxin (Journal of Ecohumanism, 2025)
This study examines the relationship between writing anxiety and performance among high school students in China who take the TOEFL writing test, focusing on the factors that lead to anxiety and the influence of demographic variables.The contrast lies in the degree of impact, whereby moderate writing anxiety has a negative correlation to TOEFL scores, whereas higher levels of anxiety was found to hamper the test. Sources of Major Anxiety Inhibitors comprise problematic writing topics, low self-confidence in their language use, time constraints, and previous bad experiences. On the other hand, the effects of evaluation on anxiety received conflicting responses and thus are a source of individual differences and cultural factors. Other demographic variables studied included age, gender, grade, years of English study, and exposure to an English-speaking environment but were studied to have limited impact on the degree of writing anxiety. Therefore, interventions based on anxiety sources rather than demographic factors are needed. Teaching implications include creating supportive learning environments; providing language-building resources and gradually introducing time-constrained tasks to build confidence. These findings contribute to the research on the impact of writing anxiety on TOEFL scores and provide practical avenues for reducing anxiety in preparation for high-stakes exams. Future research should focus on expanding the sample size to encompass diverse regions in China and investigate issues related to the relationship between self-efficacy and writing anxiety and performance, which would lead to a more beneficial understanding of how students could be assisted to enhance TOEFL performance.